The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Blackwell Handbook of Infant Development 2004
DOI: 10.1002/9780470996348.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception

Abstract: Child-Clinical Psychology, Development of Body Image, Eating Disorders and Obesity in In G. Bremner (Ed.), Blackwell handbook of infant development. Part III focuses on the early development of infants' ability to monitor others in In G. Bremner & A. Fogel (Eds.), Blackwell Handbook of Infant Development. We are studying groups of infants at-risk for autism (such as the younger siblings of In: The Wiley-Blackwell Handbook of Infant Development 2nd Edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…In effect, newborns might be unable to detect a difference between human eyes and other species’ eyes. A low-level-based capacity to detect human eyes would emerge later with the improvements in acuity, contrast sensitivity, and color vision (Slater, 2001). However, this proposal appears inconsistent with our luminance and contrast analysis showing that infants and newborns should be able to discriminate the NonHumanEyes-Face with the HumanEyes-Face (see Figure 1 and Footnote 1).…”
Section: Discussionmentioning
confidence: 99%
“…In effect, newborns might be unable to detect a difference between human eyes and other species’ eyes. A low-level-based capacity to detect human eyes would emerge later with the improvements in acuity, contrast sensitivity, and color vision (Slater, 2001). However, this proposal appears inconsistent with our luminance and contrast analysis showing that infants and newborns should be able to discriminate the NonHumanEyes-Face with the HumanEyes-Face (see Figure 1 and Footnote 1).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the longitudinal development within the first three months, we expect a significant increase of face-to-face contact in the German sample, in line with previously reported findings from Western middle-class samples (e.g., Adamson, 1995;Reddy et al, 1997). This increase is based on the infant's growing ability to return and maintain facial exchange over the first three months (Slater, 2004). Since face-to-face contact is not emphasized in Nso ethnotheories of parenting (Keller et al, 2002), we do not expect temporal variation in face-to-face contact in the Nso sample.…”
Section: The Culture Of Nso Farmer Familiesmentioning
confidence: 96%
“…Moreover, they suggested that these abilities are evolutionary in origin, implying that some sort of hereditary mechanism is likely to be involved. Slater (2004) repeated this conclusion in a review of the development of face perception by asserting that even though in utero propioceptive feedback may contribute to newborns’ representation of faces, the in utero experience interacts with “innate evolutionary biases” (p. 21). Although Slater does not specify what he means by innate evolutionary biases, others who practice the strong version of nativism are clear about this.…”
Section: Examples Of a Modern Nativist Approach And Its Limitationsmentioning
confidence: 99%